ANALISIS TINGKAT KEPUTUSAN PASIEN BPJS TERHADAP KUALITAS PELAYANAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Jumadi Suratman; , Rini Halila Nasution; Uun Novalia Harahap; Ilhamdi Syahputra; Raymond Christian Silaban (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
Research at the Harun Kuala Tanjung clinic conducted an analysis of the level of satisfaction of BPJS patients with the quality of service, which so far in the service activities carried out there are still complaints. Therefore, it is necessary to analyze the interests or satisfaction of patients who can use the Quality Function Deployment (QFD) method. Based on the results of the calculation of the satisfaction level, it got a score of 8720 and obtained an average satisfaction score of 87.2. As for the results of the calculation of the improvement ratio, the value taken to be the basis for improvement in the analysis of the level of patient satisfaction with the quality of service, the value obtained was 1.3744, namely in statement/statement number 15 which contains, Knowledge and the ability of the doctor to establish the diagnosis of the disease. The value that is getting closer or the value that is most obtained means the value or statement that must be corrected. The results of the improvement rating use the calculation of the level of absolute importance and relative importance, namely conducting health training and seminars, maintaining good relations with patients, serving patients in accordance with existing procedures, being fast and responsive in handling patients, not Differentiating patient status, improving the ability to resolve patient complaints, explaining information in easy-to-understand language, being meticulous when examining patients seeking treatment, adding parker land and parker facilities. Next came the establishment of the House of Quality house. Keywords: Klinik; BPJS; Quality Function Deployment (QFD; House of Quality (HOQ)